2003
DOI: 10.1074/jbc.m307871200
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol Ester-dependent Activation of Peroxiredoxin I Gene Expression via a Protein Kinase C, Ras, p38 Mitogen-activated Protein Kinase Signaling Pathway

Abstract: The antioxidant protein peroxiredoxin (Prx) I is a thioredoxin peroxidase that is involved in the regulation of proliferation and differentiation of mammalian cells. Here, it is shown that Prx I gene expression was induced transcriptionally by the phorbol ester 12-O-tetradecanoylphorbol-13-acetate (TPA) in cultured rat liver tissue macrophages and RAW264.7 monocytic cells. TPA-dependent induction of Prx I gene expression was mediated by two proximal activator protein-1 sites of the rat Prx I promoter region th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…EPACs are guanine nucleotide exchange factors for the small G protein Rap1 (26). cAMP-dependent and phorbol ester/ PKC-dependent activations of p38, JNK, and ERK have been reported (18,21,(27)(28)(29)(30)(31). For example, h-adrenergic stimulation of p38 is blocked by a PKA inhibitor in brown adipocytes.…”
Section: Introductionmentioning
confidence: 99%
“…EPACs are guanine nucleotide exchange factors for the small G protein Rap1 (26). cAMP-dependent and phorbol ester/ PKC-dependent activations of p38, JNK, and ERK have been reported (18,21,(27)(28)(29)(30)(31). For example, h-adrenergic stimulation of p38 is blocked by a PKA inhibitor in brown adipocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanism by which it elicits these two effects is unclear, the requirement of ROS in TPA-induced toxicity has been demonstrated (Lin et al, 2006). Induction of Prdx1 by TPA in H2.35 cells is not surprising given a prior study reporting Prdx1 induction by TPA in rat liver tissue macrophages and monocytic cells through a PKC/Ras/p38MAPK pathway (Hess et al, 2003). While this study reported nearly eight-fold induction by six hours, our results suggest a more modest effect on Prdx1 in H2.35 cells.…”
Section: Regulation Of Peroxiredoxins By Tpamentioning
confidence: 99%
“…In addition to the previously mentioned consensus sequences, two putative AP1 sites are found between 340 and 470 nucleotides upstream of the transcription start site. It is worth noting that the TPA-dependent induction of Prdx1 reported by Hess et al was mediated by two proximal AP-1 sites targeted by c-Jun (Hess et al, 2003). The investigation of these potential regulatory elements and the corresponding DNA binding proteins will provide greater insight into the transcriptional regulation of Prdx6.…”
Section: Other Possible Mechanisms Of Prdx6 Regulationmentioning
confidence: 99%
See 2 more Smart Citations